The QUEST for Effective and Equitable Policies to Prevent Non-communicable Diseases: Co-Production Lessons From Stakeholder Workshops - Ffion Lloyd-Williams; Rebecca Masters; Lirije Hyseni; Emily St. Denny; Martin O’Flaherty; Simon Capewell (International Journal of Health Policy and Management, 2021)
BackgroundNon-communicable diseases (NCDs) account for some 90% of premature UK deaths, most being preventable. However, the systems driving NCDs are complex. This complexity can make NCD prevention strategies difficult to develop and implement. We therefore aimed to explore with key stakeholders the upstream policies needed to prevent NCDs and related inequalities. MethodsWe developed a theory-based co-production process and used a mixed methods approach to engage with policy- and decision-makers from across the United Kingdom in a series of 4 workshops, to better understand and respond to the complex systems in which they act. The first and fourth workshops (London) aimed to better understand the public health policy agenda and effective methods for co-production, communication and dissemination. In workshops 2 and 3 (Liverpool and Glasgow), we used nominal group techniques to identify policy issues and equitable prevention strategies, we prioritised emerging policy options for NCD prevention, using the MoSCoW approach. ResultsWe engaged with 43 diverse stakeholders. They identified ‘healthy environment’ as an important emerging area. Reducing NCDs and inequalities was identified as important, underpinned by a frustration relating to the evidence/policy gap. Evidence for NCD risk factor epidemiology was perceived as strong, the evidence underpinning the best NCD prevention policy interventions was considered patchier and more contested around the social, commercial and technological determinants of health. A comprehensive communications strategy was considered essential. The contribution of ‘elite actors’ (ministers, public sector leaders) was seen as key to the success of NCD prevention policies. ConclusionsNCDs are generated by complex adaptive systems. Early engagement of diverse stakeholders in a theory-based co-production process can provide valuable context and relevance. Subsequent partnership-working will then be essential to develop, disseminate and implement the most effective NCD prevention strategies.